Adenoid cystic carcinoma of hard palate with coincidental metastases to lung and liver. (27th February 2013) - Akhavan, Ali; Binesh, Fariba; Navabii, Hossein
Abstract : Adenoid cystic carcinoma is the most frequent pathology occurring in the minor salivary glands .It is usually slow growing; however, it can spread via perineural invasion, haematogenous and lymphatogenous metastasis. Most common sites of metastasis are lung and bone. Involvement of the other sites is not common. In this article, we present a woman with coincident lung and liver metastases.